2010
DOI: 10.1108/09596111011018223
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between transformational leadership and employee desire for empowerment

Abstract: Purpose -The purpose of this paper is to examine the relationship between transformational leadership (TL) and employee desire for empowerment (EDFE). This study also aims to extend Gill and Mathur's findings regarding improving employee dedication and pro-social behavior. Design/methodology/approach -Hospitality industry employees from Canada and India were surveyed to test the relationship between TL and EDFE in countries that differ substantially in their levels of cultural power distance. Findings -Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 22 publications
2
52
1
1
Order By: Relevance
“…In the communication and human relationship domain, the results show that the way the head department deals with the staff is based on respect and trust. This result is agreed with the result of (Gill et al, 2010), the results show that the degree functional empowerment is high and its relationship with the leadership is positive according to the exchanging respect and trust. This also agree with the study of (Kreitner & Kiniki, 1994) that shows that the innovate personality leads to interaction and exchanging views, and good relationship with others.…”
Section: The Results Discussion Of the First Questionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the communication and human relationship domain, the results show that the way the head department deals with the staff is based on respect and trust. This result is agreed with the result of (Gill et al, 2010), the results show that the degree functional empowerment is high and its relationship with the leadership is positive according to the exchanging respect and trust. This also agree with the study of (Kreitner & Kiniki, 1994) that shows that the innovate personality leads to interaction and exchanging views, and good relationship with others.…”
Section: The Results Discussion Of the First Questionsupporting
confidence: 81%
“…The study is conducted by Gill et al (2010), which aimed to test the relationship between transformational leadership, empowerment, career, and social behavior. Ways and means have been applied to workers in factories in Canada, and India to test the relationship between transformational leadership, and career empowerment in the countries for different cultural level, the results indicated that the degree of career empowerment was high with transformational leadership with regard to good treatment, and appreciated by others in those two countries, as well as there were statistical differences between workers in both countries.…”
Section: International Research In Educationmentioning
confidence: 99%
“…However, it seems that employees' willingness and motivation, especially in this case, play more important role (Ozaralli, 2003). Empowerment of employees through any ways, has lots of advantages for the organization, Advantages such as job performance improvement (Batram, Casimir, 2007), reducing mistakes and increasing the speed of decision-making (Gill et al, 2012), improving collaboration and innovation (Avey et al, 2008) that all of them lead to job performance improving. But the question is that what factors are effective in improvement of employees' empowerment level?…”
Section: Problem Statementmentioning
confidence: 99%
“…Leadership, generally, refers to the motivation and influence, practiced by competence and skilled person, on the employees and subordinate to achieve overall organizational objectives (Gill et al, 2010).…”
Section: Employee Job Satisfaction (Ejs)mentioning
confidence: 99%